Communication Strategy Patterns in Tourism to Increase Visitors (A Study on Mangrove Ecotourism Cuku Nyi-Nyi Pesawaran District) - Yudistira; Hernawan, Wawan; Poyo, M. (CONVERSE Journal Communication Science, 2025)
This research aims to analyze the communication strategy patterns in tourism to increase the number of visitors at the Cuku Nyi-Nyi Mangrove Ecotourism in Pesawaran Regency. The study uses a descriptive qualitative approach with data collection techniques including interviews, observations, and documentation. The results indicate that communication strategies through social media, word of mouth, local storytelling, collaboration with stakeholders, and local community participation have successfully formed a positive image of the destination and increased tourist visits in 2023-2024. This study utilizes the theory of Social Action, Phenomenology, and IMC as the basis for analysis. The findings show that digital, participatory, and educational communication strategies are effective in enhancing appeal and building sustainable tourist engagement.